Perspectives of teachers and food sellers on healthy canteens in Yogyakarta: A qualitative study - Hardiyanti, Marina; Hanindriyo, Lisdrianto; Widita, Elastria; Dewi, Wulan May Kusuma; A'yun, Isna Nur Qurota; Amelia, Rizka Nur; Rahmadani, Alfina Nur (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2025)
ABSTRAK Latar Belakang: Ketersediaan makanan sehat menjadi faktor penting dalam menjaga kecukupan asupan gizi harian anak di sekolah. Kantin sekolah berperan sebagai unit penting dalam menyediakan makanan bagi siswa. Namun, terdapat berbagai tantangan dalam penyelenggaraan kantin sehat, baik dari segi pemilihan makanan maupun pengelolaannya. Tujuan: Penelitian ini bertujuan untuk mengetahui perspektif dan pengetahuan guru yang bertanggung jawab terhadap program kantin sehat serta penyedia makanan kantin di sebelas sekolah yang terpilih di wilayah Provinsi Daerah Istimewa Yogyakarta.Metode: Penelitian ini menggunakan pendekatan kualitatif deskriptif. Penyusunan metode penelitian mengacu pada COREQ checklist. Sepuluh pertanyaan wawancara semi-terstruktur dikembangkan untuk menggali perspektif guru dan penyedia makanan kantin pada program kantin sehat di sekolah. Sebelas guru dan delapan penyedia makanan direkrut secara purposif dan diwawancarai selama 20–40 menit pada April–Mei 2024 di sekolah. Sembilan sekolah negeri dan dua sekolah swasta dengan tujuh diantaranya adalah sekolah dasar dan empat sekolah taman kanak-kanak di wilayah Kota Yogyakarta menjadi lokasi penelitian ini. Analisis tematik digunakan untuk mengidentifikasi tema utama dan menginterpretasikan temuan penelitian. Hasil: Empat tema utama yang mencerminkan tantangan dan strategi dalam pengelolaan kantin sehat diidentifikasi melalui respon dari partisipan. Sebagian besar partisipan menegaskan pentingnya komitmen sekolah dan regulasi yang jelas dalam menjaga kualitas dan kebersihan makanan dalam upaya mendukung keberhasilan program kantin sehat. Beberapa sekolah juga telah memiliki program makan bersama, baik itu program rutin resmi maupun bagian dari program lainnya. Belum semua kantin sehat sekolah termonitor secara rutin. Kesimpulan: Keberhasilan implementasi kantin sehat bergantung pada komitmen sekolah yang kuat dan dukungan regulasi yang jelas. Sinergi antara pihak sekolah, penyedia makanan kantin, dan pemangku kebijakan diperlukan untuk keberlanjutan program kantin sehat di sekolah. KATA KUNCI: kantin sehat;; kebijakan sekolah; sekolah sehat   ABSTRACTBackground: Healthy food availability is considered an important factor in achieving daily nutritional adequacy among school children. School canteens play a vital role in providing food, yet face numerous challenges in serving healthy choices and effective management. Objectives: this study aims to explore the view of responsible teachers for healthy canteen programs and canteen food providers at eleven schools in the Yogyakarta city area.Methods: This descriptive qualitative study followed COREQ guidelines. Ten semi-structured interview questions were developed to collect perspectives from teachers and canteen food providers regarding the school’s healthy canteen. Eleven teachers and eight canteen food providers were recruited and interviewed for 20-40 minutes on April-May 2024 in the schools. The study was conducted across eleven schools in Yogyakarta City, comprising nine public and two private institutions, with seven primary schools and four kindergartens. Thematic analysis was performed to extract the themes and interpret the result. Results: Four main themes reflecting the challenges and strategies in managing a healthy canteen were identified from the responses of participants. Most participants emphasized the importance of school commitment and clear regulations in maintaining the quality and hygiene of food to support the success of the healthy canteen program. Some schools already implement lunch programs, either a regular formal lunch program or as supporting initiatives linked to other school programs. However, not all school canteens are regularly monitored.  Conclusions: The success of implementing a healthy canteen relies on the strong commitment of the school and well-defined regulatory support. Synergy between the school, canteen food providers, and policymakers is necessary to ensure the sustainability of the healthy canteen program in schools. KEYWORD: healthy canteen; healthy school; school initiativesArticle submitted on February 02, 2025; Articles revised on April 17, 2025; Articles received on July 18, 2025; Articles available online on November 30, 2025